PENGUATAN KOMPETENSI PRAKTIS GURU OTOMOTIF MELALUI MAGANG INDUSTRI DI BENGKEL RESMI - Mujianto, Mujianto; Fani Yustiadi; Erna Yayuk (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The rapid development of modern automotive technology demands that teachers in the Light Vehicle Engineering expertise field possess practical competencies relevant to current industrial advancements. However, most automotive teachers in Vocational High Schools (SMK) still experience skill gaps due to limited practical facilities and a lack of direct exposure to the latest vehicle technologies. This study aims to describe how the implementation of industrial internship programs at authorized workshops supports the strengthening of teachers’ practical competencies, as well as to identify the challenges encountered during the internship and the strategies used to overcome them. This research employed a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. The research subjects consisted of automotive teachers participating in internship programs at authorized workshops, along with instructors or technicians serving as industrial mentors. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that the industrial internship significantly enhances teachers’ practical competencies, particularly in electronic system diagnostics, implementation of manufacturer-standard service procedures, and the use of advanced computerized equipment. In addition, teachers gained new insights into industrial work culture and customer service management. The main challenges identified include the limited duration of the internship, differences in work standards between schools and industry, and adaptation to new technologies. These challenges were addressed through intensive mentoring, flexible scheduling, and collaborative learning between teachers and industry technicians